OP78 The Role of Social Relationships in Understanding Healthful Dietary Behaviours: Evidence from People Aged 50 and over in the Epic-Norfolk Cohort. (10th September 2013) - Conklin, A; Forouhi, N; Wareham, N; Monsivais, P
Abstract : Background: Social relationships are an integral aspect of a person's social environment that may offer protection against chronic conditions and may facilitate recovery from disease. Social relationships have also been linked to dietary behaviour which may be an important pathway through which social circumstances impact health. Yet, questions remain about which aspects of social ties most influence healthful dietary behaviours among women and men and to what extent different types of social ties interact to produce a combined influence. Methods: Using prospective data from adults (≥50 years) in the European Prospective Investigation of Cancer-Norfolk (EPIC-Norfolk) study, multivariable linear regression analysis was used to examine sex-specific associations between structural social ties (marital status, living arrangement, friend contact, family contact) and a dietary score for variety of fruits (ranging between 0–11) or vegetables (0–26). Separate interaction models tested whether overall effects of marital status changed by living arrangement or by friend contact, and of living arrangement by friend contact. All analyses adjusted for known confounders (energy intake, age, education and, where appropriate, sex). Results: Negative associations of non-partnered or lone-living persons and fruit variety were stronger in men than women, compared with those who were partnered or in shared-living. Women and men differed in the negative association of widowhood with vegetable variety (women: Beta = −0.79, p < 0.001; men: Beta = −2.17, p < 0.001), as well as in the relationship between lone-living and vegetable variety (women: Beta = −0.66, p < 0.001; men: Beta = −1.46, p < 0.001). Decreasing friend contact was negatively associated with variety of fruits and vegetables in a graded trend for women but was stronger in men. Family contact appeared to have no association with vegetable variety in men while variety scores in women were initially positive but decreasing with decreasing contact. Results were most striking in revealing the combined influence of two types of social ties in relation to variety when looking at both sexes together. For example, the negative association of lone-living with vegetable variety was significantly different ( p = 0.007) between infrequent friend contact (Beta = −1.62; p < 0.001) and frequent contact (Beta = −0.80; p < 0.001). Conclusion: Variety scores of men were more influenced than those of women by marital status, living arrangement or friend contact. Interactions between two social ties were striking, revealing the combined influences on healthful dietary behaviours. Results highlight the importance of considering living arrangement and frequency of social contact when assessing whether widowed or single older adults are at risk of lower fruit and vegetable variety.